Effect of explant type on the rooting and acclimatization of Dianthus serotinus Waldst. & Kit. - Marković Marija; Grbić Mihailo; Skočajić Dragana; Đukić Matilda (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2014)
The effect of the concentration of MS salts and explant type on D. serotinus rooting and acclimatization was investigated in order to optimize a protocol for the micropropagation of this species. The obtained results showed that explant type as well as the concentration of MS salts had a significant effect on rooting, and the highest rooting rate (85-86,7%) was achieved when culturing single-node cuttings and terminal buds on a half-strength MS medium supplemented with 0,5 mgL-1 NAA. Nevertheless, mean number of roots per explant was higher on the MS media (15,3-18,6) than on the half-strength MS media (11,8-13,4). The best acclimatization rate was obtained in a 4:1 mixture of peat and sand (83,3-86,7%). The explant type from which in vitro plantlets developed had no effect on the acclimatization rate. [Projekat Ministarstva nauke Republike Srbije, br. 43007]